2023
DOI: 10.1002/ajhb.23958
|View full text |Cite
|
Sign up to set email alerts
|

Coping mechanisms during the COVID‐19 pandemic and lockdown in metropolitan Johannesburg, South Africa: A qualitative study

Nerli Paredes Ruvalcaba,
Andrew Wooyoung Kim,
Nokubonga Ndaba
et al.

Abstract: BackgroundThe COVID‐19 pandemic has caused prolonged stress on numerous fronts. While the acute health impacts of psychosocial stress due to the pandemic are well‐documented, less is known about the resources and mechanisms utilized to cope in response to stresses during the pandemic and lockdown.ObjectiveThe aim of this study was to identify and describe the coping mechanisms adults utilized in response to the stressors of the COVID‐19 pandemic during the 2020 South African lockdown.MethodsThis study included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Social support was one of the most endorsed coping strategies [ 15 ], which is notable in the role that relationships may play in decreasing the risk of mortality [ 44 ] and mental health issues [ 45 , 46 ]. Family support specifically has been linked with increased active coping [ 47 ] and decreased emotional exhaustion [ 48 ], perhaps providing an explanation for its importance in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…Social support was one of the most endorsed coping strategies [ 15 ], which is notable in the role that relationships may play in decreasing the risk of mortality [ 44 ] and mental health issues [ 45 , 46 ]. Family support specifically has been linked with increased active coping [ 47 ] and decreased emotional exhaustion [ 48 ], perhaps providing an explanation for its importance in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on community‐based samples and healthcare workers have found similar adverse psychological outcomes due to pandemic‐related stressors, including elevated risks for adult depression, anxiety, post‐traumatic stress disorder, and bipolar disorder (De Man et al, 2022; Engelbrecht et al, 2021; Kim et al, 2021; Kim et al, 2023). Researchers have also identified the buffering and protective effects of positive social experiences against pandemic‐related stress, including individual coping, social support, health education, and adaptations to clinical practice, to maintain psychological well‐being (Engelbrecht et al, 2021; Kim et al, 2023; Paredes‐Ruvalcaba et al, 2023; Scheunemann et al, 2023). Nevertheless, active SARS‐CoV‐2 transmission, chronic shortages in mental healthcare infrastructure, and the persistence of the psychological, health, and socioeconomic repercussions of the pandemic raise pressing concerns about the current mental health burdens of the pandemic in South Africa (Docrat et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“… 22 Persons considered to be particularly vulnerable, for example, the elderly, the immune compromised and those with cancer were required to shield for weeks or months on end, often to the detriment of their mental and physical health. 23 However, whether these NPIs had a significant benefit on case growth is the subject of ongoing research. 24 …”
Section: Introductionmentioning
confidence: 99%
“…22 Persons considered to be particularly vulnerable, for example, the elderly, the immune compromised and those with cancer were required to shield for weeks or months on end, often to the detriment of their mental and physical health. 23 However, whether these NPIs had a significant benefit on case growth is the subject of ongoing research. 24 Healthcare facilities and personnel were so overwhelmed with caring for patients with COVID-19 that many routine services, and even cancer screening and treatment, were severely reduced or stopped altogether.…”
Section: Introductionmentioning
confidence: 99%